Visions Project K.1: DIY 3-D interactive videohologram device. (22nd December 2014) - Mereu, Francesca; Villarroel, Javier
The Visions Project K.1 is an interactive video installation that, inspired by science fiction movies and the new digital sets from recent years, uses the aesthetics of digital hologram to create 3-D portraits. The portraits are processed in real time and are displayed in a volume of three-dimensional points that the Microsoft Kinect camera records through a depth sensor based on the spatial coordinates of the public participant. These are projected onto a pyramidal structure with an LCD monitor, and due to the special geometry of the structure, appear to be real 3-D objects floating inside the pyramid. The modular design of the components of the structure enables the user to build their own device, Do It Yourself (DIY).